2014
DOI: 10.1007/s12274-014-0561-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of photoresponsive electrical characteristics of multilayer MoS2 transistors using rubrene patches

Abstract: Multilayer MoS 2 is a promising active material for sensing, energy harvesting, and optoelectronic devices owing to its intriguing tunable electronic band structure. However, its optoelectronic applications have been limited due to its indirect band gap nature. In this study, we fabricated a new type of phototransistor using multilayer MoS 2 crystal hybridized with p-type organic semiconducting rubrene patches. Owing to the outstanding photophysical properties of rubrene, the device characteristics such as cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
1
18
0
3
Order By: Relevance
“…In the second type of hybrid device, the sensitizers that are employed to enhance light absorbance or to extend the detection range are normally quantum dots (QDs), organic molecules, and CH 3 NH 3 PbI 3 perovskite . For example, Kufer et al reported a hybrid photodetector composed of bilayer MoS 2 covered with 1,2‐ethanedithiol ligands and (EDT)‐capped colloidal PbS QDs .…”
Section: Photoconductors/phototransistors Based On 2d Layered Semiconmentioning
confidence: 99%
“…In the second type of hybrid device, the sensitizers that are employed to enhance light absorbance or to extend the detection range are normally quantum dots (QDs), organic molecules, and CH 3 NH 3 PbI 3 perovskite . For example, Kufer et al reported a hybrid photodetector composed of bilayer MoS 2 covered with 1,2‐ethanedithiol ligands and (EDT)‐capped colloidal PbS QDs .…”
Section: Photoconductors/phototransistors Based On 2d Layered Semiconmentioning
confidence: 99%
“…The low on/off current ratio of graphene, which is a result of its semimetallic nature, makes it unsuitable for FET applications. Therefore, many researchers have been interested in layered semiconducting materials such as TMDCs for hybridization with organic molecules . Kang et al demonstrated an ultrahigh‐performance MoS 2 –CH 3 NH 3 PbI 3 phototransistor with record photoresponsivity (Figure f) .…”
Section: Electronic and Optoelectronic Applicationsmentioning
confidence: 99%
“…[22,38,42] , 容易得到大面积的样品, 但不容易得到高 良、 性能更稳定的器件 [43,44] , 但目前有机-无机异质结 器件中这种器件类型的报道还比较少. 国际上绝大 部分研究组已报道的相关工作都是基于背栅的场效 应晶体管(FET)结构 [6,8,11,13,23,45] . 最近的一些研究表明, 有机无机异质结在未来 的器件应用上具有优异的潜力 [6,12,17,25,41,47,48] .…”
Section: 这类材料具有没有块体分隔的两个表面 因此拥有unclassified